Navigating co-design of actor-networks. (10th June 2023) - Pedersen, Signe; Brodersen, Søsser
In this paper, we illustrate the importance of involving different types of users in collaborative design and innovation processes to allow end-users to speak on their own behalf. However, involving multiple actors with diverse concerns requires designers to carefully stage spaces for negotiation. Through a case study of the design of a pilot program to make insulin more accessible to marginalised diabetes patients in India, we explore how designers navigate the design process by staging and facilitating several spaces for negotiation populated by patients with diabetes, doctors, company representatives, design games and management templates.